Forgotten frontline workers: Environmental health service employees' perspectives on working during the COVID‐19 pandemic. Issue 3 (15th February 2022) - Jordan, Sarah R.; Daddato, Andrea E.; Patel, Hemali P.; Jones, Christine D.
Abstract: Background: Environmental Health Service employees (EVS) sanitize healthcare facilities and are critical to preventing infection, but are under‐resourced during the COVID‐19 pandemic and at risk of burnout. Objective: Understand demands on EVS' work and strain on resources during COVID‐19. Design: Qualitative descriptive study conducted in winter 2020–2021. Setting: One quaternary care academic medical center in Colorado. Participants: A convenience sample of 16 EVS out of 305 eligible at the medical center. Fifty percent identified as Black, 31% as Hispanic, 6% as Asian, and 6% as White (another 6% identified as mixed race). Sixty‐nine percent were female, and half were born in a country outside the United States. Measures: Semistructured telephone interviews. Interviews were audio‐recorded and transcribed, and thematic analysis was used to identify key themes. Results: Four themes illustrate EVS experiences with job strain and support during COVID‐19: (1) Needs for ongoing training/education, (2) Emotional challenges of patient care, (3) Resource/staffing barriers, and (4) Lack of recognition as frontline responders. Despite feeling unrecognized during the pandemic, EVS identified structural supports with potential to mitigate job strain, including opportunities for increased communication with interdisciplinary colleagues, intentional acknowledgment, and education for those who speak languages other than English. Strategies that can increase physical and emotional resources and reduce job demands have potential to combat EVS burnout. Conclusions: As the surge of COVID‐19 cases continues to overwhelm healthcare facilities, healthcare systems and interdisciplinary colleagues can adopt policies and practices that ensure lower‐wage healthcare workers have access to resources, education, and emotional support.